Out-of-field in vivo dosimetry using TLD in SABR for primary kidney cancer involving mixed photon fields. (May 2017) - Lonski, P.; Keehan, S.; Siva, S.; Pham, D.; Franich, R.D.; Taylor, M.L.; Kron, T.
Highlights: In vivo dosimetry performed using TLD on ten SABR patients. Measured photon dose compared to treatment planning system (TPS) calculations. TPS found to under-estimate out-of-field dose. Additional TLD signal detected due to neutrons from high energy radiotherapy. Further work required to interpret neutron TLD signal. Abstract: Purpose: To assess out-of-field dose using three different variants of LiF thermoluminescence dosimeters (TLD) for ten patients who underwent stereotactic ablative body radiotherapy (SABR) for primary renal cell carcinoma (RCC) and compare with treatment planning system (TPS) dose calculations. Methods and materials: Thermoluminescent dosimeter (TLD) measurements were conducted at 20, 30, 40 and 50 cm from isocentre on ten patients undergoing SABR for primary RCC. Three types of high-sensitivity LiF:Mg, Cu, P TLD material with different 6 Li/ 7 Li isotope ratios were used. Patient plans were calculated using Eclipse Anisotropic Analytical Algorithm (AAA) for clinical evaluation and recalculated using Pencil Beam Convolution (PBC) algorithm for comparison. Results: Both AAA and PBC showed diminished accuracy for photon doses at increasing distance out-of-field. At 50 cm, measured photon dose was 0.3 cGy normalised to a 10 Gy prescription on average with only small variation across all patients. This is likely due to the leakage component of the out-of-field dose. The 6 Li-enriched TLD materials showed increased signal attributable to additional neutron contribution. Conclusion: LiF:Mg, Cu, P TLD containing 6 Li is sensitive enough to measure out-of-field dose 50 cm from isocentre however will over-estimate the photon component of out-of-field dose in high energy treatments due to the presence of thermal neutrons. 7 Li enriched materials which are insensitive to neutrons are therefore required for accurate photon dosimetry. Neutron signal has been shown here to increase with MUs and is higher for patients treated using certain non coplanar beam arrangements. Further work is required to convert this additional neutron signal to dose.